COMPARATIVE ANALYS OF CULTURAL CONCEPTS IN ENGLISH AND UZBEK LITERARY TEXTS AND THEIR TRANSLATION - Xoldorova Shahlo Shuhratjon qizi (TADQIQOTLAR, 2025)
Abstract. This study investigates the linguistic and cultural dimensions of English and Uzbek literary texts through a comparative lens, focusing on how culturally specific concepts are represented and translated. The research draws on the interdisciplinary frameworks of comparative literature, contrastive linguistics, and translation studies. Selected novels and short stories by English and Uzbek authors are analyzed to identify common themes, language structures, and translation strategies. The study highlights how cultural and linguistic differences influence literary meaning and how translators manage the challenge of maintaining cultural authenticity while ensuring readability. Findings reveal that certain concepts, such as kinship, hospitality, and spirituality, are deeply rooted in cultural identity and require creative translation strategies, including adaptation, domestication, and explanatory commentary. The research emphasizes that translation is both an art and a science, involving a balance between fidelity to the source text and sensitivity to the target culture.